Morfometri dan Ultrastruktur Cacing Fasciola gigantica pada Sapi Donggala dan Sapi Bali di Kabupaten Berau, Kalimantan Timur (MORPHOMETRY AND ULTRASTRUCTURAL OF FASCIOLA GIGANTICA WORM IN DONGGALA AND BALI CATTLE IN BERAU DISTRICT, EAST KALIMANTAN) - Prasetya, Muhammad Rofi'; Lastuti, Nunuk Dyah Retno; Suwanti, Lucia Tri; Koesdarto, Setiawan; Kusnoto, Kusnoto; Yunus, Muchammad (Jurnal Veteriner; Vol 20 No 2 (2019)DO - 10.19087/jveteriner.2019.20.2.171, 2019)
Fasciolosis is one of the endemic parasitic diseases in Indonesia. Fasciola gigantica is the main species found to infect livestock, especially beef cattle. The purpose of this study was to analyze the morphometry and identify the ultrastructure morphology of the F. gigantica worm isolated from beef cattle in Berau abattoir.  The F. gigantica worms were isolated from two cattle breeds, namely Donggala cattle and Bali cattle. Worm was stained by using carmine methode to analyze the morphometric of the worm and  scanning electron microscopy  to identify ultrastructure morphology. Morphometric of the worm was analysed with the one sample t-test and multidimensional scaling statistical methods. The results of the morphometric analysis showed that F. gigantica from both breeds had significant differences (P<0.05) between the parameters and based on multidimensional scaling analysis had similarities with F. intermedia from Iran. Based on scanning electron microscopy examination showed that F. gigantica from the Donggala cattle breed was infected with type 1 of F. gigantica while F. gigantica from the Bali cattle breed was infected with type 2 of F. gigantica based on ventral sucker, oral sucker, and spine. It can be concluded that F. gigantica found in beef cattle in Berau was type 1 F. gigantica (Donggala cattlebreed) and type 2 F. gigantica (Bali cattle breed) and similar with F. intermedia from Iran.